Fatty legs : a true story - Jordan-Fenton, Christy; Pokiak-Fenton, Margaret (Annick Press, 2020)
Eight-year-old Olemaun begs her father to allow her to leave her Arctic home and attend school in order to learn to read. At school the nuns take away her Inuit name, cut off her braids, and force her to do manual labor. But brave Olemaun stands tall and teaches herself to read in spite of the meanness of those around her.